Further Analysis of Non-Gaussian Wind Pressure Peak Factor Calculation - Tao Ye; Ledong Zhu; Zhongxu Tan; Lanlan Li (Advances in Civil Engineering)
The wind pressure time history of high-rise building cladding is mostly non-Gaussian distribution, and there is a one-to-one correspondence between a specified guarantee rate and its corresponding peak factor. A stepwise search method for calculating the peak factor of non-Gaussian wind pressure and a gradual independent segmentation method for extracting independent peak values have been proposed to determine the relationship accurately in the previous study. Based on the given experiment and calculation results in the existing research results, more analysis can be given to enrich the study on this topic. In this paper, some characteristics of wind pressure coefficient time series in time and frequency domain are analysed. Based on the basic theory of fractal, the R/S analysis of wind pressure time series is made, and the fractal characteristics of wind pressure coefficient time series are explained. Based on the statistical theory, the relationship characteristics between high-order statistics and peak factors are studied. The correlation between the guarantee rate and the corresponding peak factor is analysed, and the guarantee rates calculated by the Davenport peak factor method are evaluated. The power spectrum characteristics of fluctuating wind pressure are analysed and the relationship between turbulence characteristic frequency and optimal observation time interval is discussed.